Guía Docente para utilizar el Museo del Agua Yaku y el Museo de la Ciudad como recurso para la enseñanza-aprendizaje del entorno natural y social en tercero de Educación Básica - Zavala Chávez, Carmen Alexandra (2010)
This product is a proposal to use the City Museum and the Museum of Water (Yaku) through the process of teaching and learning the natural and social environment for children from third base. This product tries to be a tool for teaching basic third, allowing work creatively in visits to museums before, during and after it. To which is taken as a reference to the following authors: Jean Piaget, Lev S. Vygotsky, Arnold Gesell, David Ausubel, Erikson and the Consensus Proposal Module Curriculum Reform of Basic Education.